PARALLELISM AS A STYLISTIC FIGURE IN CHARLOTTE BRONTE‟S WORK “JANE EYRE” - Dauletmuratova, X.E. (SCIENCE and SOCIETY, 2025)
This article analyzes parallelism as a stylistic device in Charlotte Bronte's works, focusing on the novel «Jane Eyre». It examines syntactic, anaphoric, epiphoric, chiastic, and semantic types of parallelism, exploring their role in the social critique of Victorian norms and the psychological portrayal of women. Parallelism is considered as a tool that enhances the feminist narrative and reveals the inner conflicts of the female characters.